2010
DOI: 10.1002/app.31476
|View full text |Cite
|
Sign up to set email alerts
|

Electropolymerization of p‐phenylenediamine on Pt‐electrode from aqueous acidic solution: Kinetics, mechanism, electrochemical studies, and characterization of the polymer obtained

Abstract: Electropolymerization of p-phenylenediamine (pPD) on Pt-electrode from a deoxygenated aqueous acid medium was carried out using cyclic voltammetry technique. The kinetic parameters were calculated by means of electrochemical data. The experimentally obtained kinetic equation was1.23 [acid] 1.24 [electrolyte] 0.94 from the value of the anodic current density. The apparent activation energy (E a ) is found to be 65.1 kJ mol À1. The obtained polymer films have been characterized by X-ray diffraction, elementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 32 publications
6
27
0
Order By: Relevance
“…Such electrochemical behavior was previously observed during the electropolymerization of PPD on Pt electrodes [29,35], but also during the electropolymerization of other amines, for example ethylenediamine [38] or 1,3-diaminopropane [39]. Thus, it was shown that the anodic oxidation of PPD leads to the formation of poly(p-phenylenediamine) on platinum electrode.…”
Section: Electrodeposition Of Poly(p-phenylenediamine) Filmssupporting
confidence: 57%
See 1 more Smart Citation
“…Such electrochemical behavior was previously observed during the electropolymerization of PPD on Pt electrodes [29,35], but also during the electropolymerization of other amines, for example ethylenediamine [38] or 1,3-diaminopropane [39]. Thus, it was shown that the anodic oxidation of PPD leads to the formation of poly(p-phenylenediamine) on platinum electrode.…”
Section: Electrodeposition Of Poly(p-phenylenediamine) Filmssupporting
confidence: 57%
“…When compared to the large number of papers that have been written on the electropolymerization of aniline it is clear that relatively little work has been done on the polymerization of pphenylenediamine. The main studies concerned its polymerization mechanism [29], deposition kinetics [35], electrochemical properties [35] and spectroscopic properties [29,36,37].…”
Section: Introductionmentioning
confidence: 99%
“…of the formation process does not shift with increasing number of cycles, indicating that the oxidation reactions were independent of the copolymer thickness [31,36,37].…”
Section: Electrochemical Copolymerizationmentioning
confidence: 90%
“…On reversing the potential scan, the anodic current is very small indicating the presence of a copolymer film well adhered to the Pt surface [30,31]. The absence of any cathodic peaks indicates totally irreversible system as a result of the strong adhesion of the copolymer film to Pt surface.…”
Section: Electrochemical Copolymerizationmentioning
confidence: 99%
See 1 more Smart Citation